Institutional Readiness and Digital Service Quality as Determinants of Entrepreneur Trust in Risk Based Business Licensing Services - Tunggul Sihombing; Medlin Anggreyni Hura; Asima Yanty Siahaan (Bright Publisher, 2026)
This study examines digital licensing governance in risk-based business licensing services by integrating institutional readiness, digital service quality, service dependability, procedural transparency, public trust, entrepreneur satisfaction, and compliance intention. A quantitative explanatory design was applied using 300 valid responses from entrepreneurs who had used local government licensing services and the Online Single Submission system. The respondent profile shows that 73.0% were micro and small enterprises, 60.7% operated in medium- and high-risk categories, 50.4% used assisted online services at the DPMPTSP office, and 38.3% experienced permit processing durations of more than seven days. The measurement model demonstrated strong validity and reliability, with Composite Reliability values ranging from 0.908 to 0.936 and AVE values ranging from 0.663 to 0.701. The structural model revealed that institutional readiness significantly affected digital service quality and service dependability, while digital service quality strongly influenced service dependability and procedural transparency. Procedural transparency had the strongest direct effect on public trust, with a path coefficient of 0.547, followed by entrepreneur satisfaction toward compliance intention at 0.511 and public trust toward entrepreneur satisfaction at 0.452. Mediation analysis confirmed that digital service quality contributed to satisfaction through service dependability, procedural transparency, and public trust. The findings show that digital licensing reform does not depend solely on system availability, but on the alignment of institutional capacity, digital quality, reliable service delivery, transparent procedures, and public trust. This study contributes a comprehensive governance model for explaining how digital public services strengthen satisfaction and formal compliance among entrepreneurs.